1991
DOI: 10.1227/00006123-199105000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Fossa Ependymomas: Report of 30 Cases and Review of the Literature

Abstract: Thirty patients with histologically confirmed posterior fossa ependymomas operated on between January 1976 and December 1988 were reviewed. The median age was 44 years (range, 1-69 yr). There were 7 children (aged 5 yr or younger) and 23 adults (aged 16 yr or older). There were 18 female patients and 12 male patients. Headache, nausea and vomiting, and disequilibrium were the most frequent symptoms. The most common findings were ataxia and nystagmus. Gross total resection was performed in 8 patients (27%), sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
73
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 130 publications
(79 citation statements)
references
References 0 publications
5
73
1
Order By: Relevance
“…9,10,15,16,18,19 The findings in the current study (5-year OS, 67%; 10-year OS, 50%) were similar. Results also were comparable with respect to 5-and 10-year FFS rates, which were 43% and 24%, respectively, in the current series and 42-55% and 27-43%, respectively, in the literature.…”
Section: Prognostic Factorssupporting
confidence: 78%
See 4 more Smart Citations
“…9,10,15,16,18,19 The findings in the current study (5-year OS, 67%; 10-year OS, 50%) were similar. Results also were comparable with respect to 5-and 10-year FFS rates, which were 43% and 24%, respectively, in the current series and 42-55% and 27-43%, respectively, in the literature.…”
Section: Prognostic Factorssupporting
confidence: 78%
“…Although a clear correlation between age and outcome has not been demonstrated, adult patients appear to exhibit at least a trend toward more favorable prognosis relative to pediatric patients; 5-year survival rates consistently are greater than 50% for adult patients, whereas they range from 14% to 60% for pediatric patients. 9 -13 It also has been suggested that pediatric ependymomas may behave more aggressively because of the immaturity of neural tissue in children 9,13 and that agerelated differences in outcome may be based on differences in cytogenetic aberration patterns between younger and older patients. 14 In addition, considerations regarding side effects and treatment tolerability are quite different for pediatric patients and adult patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations